Studi Literatur: Quantum Learning Sebagai Upaya Meningkatkan Hasil Belajar Siswa - Rachman Hakim; Neviyarni; Herman Nirwana (eductum: Jurnal Literasi Pendidikan, 2022)
In an effort to improve student learning outcomes, the purpose of this research is to determine the increase in learning outcomes caused by the quantum learning learning model. In this study, the "library research" method of literature analysis was used to complete the analysis of various sources used through a literature review. To gather information for this literature review, the findings of E-journal non-test tracking studies were first examined. This is done using indexed journal articles, books, theses, and online materials relevant to the use of quantum learning. The Quantum Learning approach makes learning very interesting and fun while significantly increasing student learning outcomes. The application of the Quantum Learning learning paradigm in the classroom can improve student learning outcomes in mathematics, according to the research findings.